Gaya Bahasa al-Iltifat al-Mu’jami dalam al-Qur’an - Noor, Damhuri Dj. (Arabiyatuna: Jurnal Bahasa Arab, 2020)
This article studies about aspects of al-iltifat al-mu’jami as one style of language in the Qur'an.  This study aims to reveal the secrets of meaning behind the use of two synonymous words interchangeably in one or more plots of speech. This type of research is a library research with an interdisciplinary approach. In data analysis using content analysis by examining the basic meaning of words that experience al-iltifat, then confirms the meaning through balaghah, syntactic, morphological, and semantic analysis. The results of the research show that there are two different styles of al-iltifat al-mu’jami in the Qur'an, namely: first, the transition of the use of a word to another word that is synonymous in a verse or series of verses in a plot of speech; and second, is the use of two words that are synonymous in a separate surahs in the same speech theme. The transitional use of the word among others is aimed at emphasizing a concept, emphasizing the difference in quality and quantity of something, affirming the nature to be highlighted, expanding the concept being talked, or perfecting the concept that is the theme of the speech. The benefits of studying about al-iltifat al-mu'jami are helping to understand the message of the Qur'an, dismissing the assumptions of the language of the Qur'an, understanding the other side of the miracles of the Qur'an, helping in carrying out a mindfulness towards the Qur'an, and developing insights on various approaches that can be used in developing Qur'anic studies from the linguistic side.